Bacteriological studies at Kranji catchment - Koo, Zhi Han. (2010)
A study was conducted to further investigate the source of high bacterial concentration level from high density residential area, KC02 from Kranji catchment and to gather information on how different urban land area compositions influence water quality. In this investigation, a field study was carried out in December 2009 at KC02. It was found that 11 out of 13 samples collected exceeded the safety water quality guideline of 235 CFU per 100 ml for E. coli concentrations. Most samples have Total coliforms concentrations exceeded the amount of 241, 960 CFU per 100 ml. This indicates possibility of leaking sewer pipes or damaged fitting for pipes to the drainage systems around KC02. Based on different compositions of urban land use, it was found that as the median of E. coli and Total coliform concentrations increase, the percentage of residential land use decreases. For E. coli concentration as a function of residential type of land use, it was also observed that samples containing institutional type of land use displayed the highest median E. coli concentration of 6, 340 CFU per 100 ml. For Total coliform concentration as a function of residential type of land use, it was found that samples that containing more than 50% residential type of land use displayed the highest Total coliform concentration of 73, 040 CFU per 100ml. It was also observed that agriculture type of land use of 773, 988 CFU per 100 ml has higher E. coli median concentrations as compared to STP type of land use of 2, 200 CFU per 100 ml when the expected result was STP type of land use to have the highest bacterial concentration among the four main types of land use. The findings from this study help in establishing appropriate measure to control the bacterial concentration within the urban area thus solving the pollution caused by urban runoff.